Penerapan Model Pembelajaran Quiz Team Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Geografi Kelas X Di MAN 8 Jombang - Aliffia Rina Wati; Jani Jani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated by the tendency of students to pay attention to the teacher when explaining the material, the low activity of students in re-explaining the material that has been conveyed by the teacher this is due to the low learning outcomes of students, so this can affect the learning outcomes obtained from the cognitive domain, psychomotor domain, students' affective domain. Therefore, by applying the quiz team learning model, students are expected to grow maximum learning outcomes. The focus of the research is: (1) What are the steps for implementing geography learning using the quiz team model to improve the learning outcomes of class X students at MAN 8 Jombang?, (2) What are the supporting and inhibiting factors in implementing geography learning using the quiz team model? to improve the learning outcomes of class X students at MAN 8 Jombang?, (3) What is the impact of implementing Geography learning using the quiz team model to improve student learning outcomes at MAN 8 Jombang?, The research objectives (1) To find out how the implementation steps Geography learning by using the Quiz Team model to improve student learning outcomes at MAN 8 Jombang, (2) To find out the supporting factors and inhibiting factors in the implementation of Geography learning by using the Quiz Team model to improve class X student learning outcomes at MAN 8 Jombang, (3 ) To find out how the impact of implementing Geography learning by using the quiz team model to improve student learning outcomes in class X at MAN 8 Jombang. This research uses a qualitative approach to the type of descriptive research. Descriptive research is presented in the form of words found from observations which are then analyzed, interpreted, and drawn a conclusion. The population in this study were students of class X IPS 3 MAN 8 Jombang and school residents. Data collection techniques using interviews, observation, and observation. The results of the research were taken from the conclusions which showed that the application of the quiz team learning model could improve student learning outcomes which would later influence student learning outcomes to be more optimal.